Capturing the state of the science to change the state of the science: A categorization approach to integrative reviews. (5th August 2020) - Dwertmann, David J. G.; van Knippenberg, Daan
Summary: Integrative reviews, reviews of an area of research that not only describe the state of the science but also advance it through integration and synthesis of the evidence, make unique contributions to the literature. We discuss this unique value of integrative reviews, highlighting that integrative reviews of the literature are positioned in the conceptual space between descriptive reviews and theory papers, to position this study's focus: presenting an approach to conduct such reviews. This approach focuses on the systematic consideration of similarities and differences between findings, identifying the underlying categorizations that capture these similarities and differences, and developing new theory anchored on these categorizations for similarities and differences not predicted by existing theory. We outline how authors following this approach should make the different steps in this process of categorization and theory development transparent in their presentation to increase replicability of the review and more precisely identify the locus of potential disagreements concerning the conclusions of the review. Following these steps also provides clearer anchors to assess the validity of the conclusions of the review in the publication process, for readers, and in follow‐up primary research.